Rest energy expenditure in Parkinson's disease: Role of disease progression and dopaminergic therapy - Capecci, Marianna; Petrelli, Massimiliano; Emanuelli, Benedetta; Millevolte, Marzia; Nicolai, Albano; Provinciali, Leandro; Ceravolo, Maria Gabriella (Parkinsonism & related disorders, 2013)
Weight loss affects more than 50% of subjects suffering from Parkinson's Disease (PD) and is associated with reduced life expectancy. The pathogenesis is multifactorial and the mechanism of PD metabolism control is unresolved. This cross-sectional study aimed to ascertain the relationship between rest energy expenditure (REE), PD duration, Hoehn & Yahr (H&Y) stage, drug therapy and body mass index (BMI), in order to determine possible predictors of weight loss. We studied fifty-eight PD subjects, after excluding conditions with a known influence on metabolism and weight (severe tremor, dyskinesias, dementia, fever, on-going infections, thyroid disease, and dysphagia). Subjects underwent REE measurement, through indirect calorimetry, in both the OFF state (12 h fasting and off medications) and in the ON state (60 min after taking dopaminergic drugs). OFF state. In the majority of PD patients REE values did not differ from those expected (based upon age, gender and BMI), being significantly higher in subjects in H&Y stage IV than H&Y stage II (t = 3.5; p = 0.001). Disease duration and rigidity were significantly associated with increased REE (r2 = 0.31, F = 3.6; p = 0.0045). ON state. REE decreased by approximately 8% in all subjects, irrespective of disease duration or H&Y stage. BMI was inversely related to disease duration and UPDRS motor score in the OFF state and directly related to UPDRS motor score in the ON state (r2 = 0.333, F = 3.5; p = 0.003). In PD REE increases as a function of disease duration; its adverse role in the decrease in BMI seems to be compensated for by dopaminergic medication.